The effect of carbopol 940 on physical stability of palm olein emulsions stabilised by span and tween surfactants - Mohd. Nawi, Mohamed Sufian; Ahmad, Kausar (2008)
Viscosity inducing agents are commonly used to modify the rheological properties of emulsions. The objective of the study was to determine the effects of the concentration of Carbopo1 940 on the physical stability and rheological properties of palm olein-in-water emulsions prepared with Span 20/Tween 20 and Span 20/Tween 80. Based on the creaming behaviour and particle size analysis, 0.1 to 0.3% (w/w) of Carbopo1 940 was found to be suitable for the further stabilisation of the emulsions with Span 20/Tween 20. However, the emulsions with a combination of Carbopol 940 and Span 20/Tween 80 were not stable. Destabilisation could have resulted from the depletion of water molecules as a result of further hydration of hydrophilic Carbopol 940 and thus adversely affected the hydration of the hydrophilic moieties of the non-ionic surfactants used. This tendency is suspected to be more prominent for the Tween 80 as it is less hydrophilic than Tween 20. The stable emulsions produced exhibited viscoelastic and pseudoplastic behaviour with yield stress. Within the linear viscoelastic region, the emulsions were elastic in nature. Desired rheological properties can be obtained by changing the concentration of Carbopol 940 to make it suitable for the development of topical cream and lotion.